Election Socialization Through a Cross-Cultural Communication Approach - Hasrat Efendi Samosir (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this article is to reveal how the socialization of elections through a cross-cultural communication approach, in many ways, the relationship between culture and communication is reciprocal. This research method uses a qualitative research approach. The results of this study are that in the context of election socialization as an alternative solution to dealing with high levels of society who are apathetic and not exercise their right to vote or Abstentions (white group), an approach using cross-cultural communication is very appropriate to be used as a model and offer so that people are closer and have sensitivity and concern high expectations for each election event to produce better leadership, the descriptions above are still in the nature of an offer which, if further formulated, will become an alternative model for socializing elections to the public. Finally people realize the essence of democracy itself; of the people, by the people and for the people.